Efektifitas Metode V Shape Loading Dengan Cross Loading Terhadap Produktivitas Whell Loader - Dzakir, La Ode (Jurnal of Mining Insight, 2024)
The research was conducted in regency of Taliabu Island, North maluku province on mining problem studied in this research is to calculate the effectiveness of loading tool production using two methods, namely cross loading and V Shape loading. To solve the problem, firstly do the calculation on the productivity of each of the two methods, such as calculation of cycle time, Fill Factor, Sweel Factor and work efficiency of loading tools. The cycle time from V shape loading method is 30.07 seconds and the cross loading method is 37.40 seconds, the fill Factor for shape loading method is 83% while for the cross loading method is 84%, its Sweel Factor is 80% and the work efficiency from theV Shape Loading method is 79%, while the cross loading method is 76%. Based on results, the effectiveness of the production of V Shape loading method is 308,85 tons/hour while the cross loading method is 248,59 tons/huor.